Obstetric hysterectomy: a surgical emergency 3 years review in a tertiary care centre - Sah, Shanti; Gupta, Shipra (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Obstetric haemorrhage is a life threatening complication associated with increased maternal morbidity and mortality. Its incidence is 0.2-4 per 1000 deliveries in developed countries and much higher in developing countries. The main cause still remains rupture uterus, postpartum hemorrhage (PPH) and placenta accreta spectrum (PAS). Methods: A retrospective analysis of obstetric hysterectomies performed over a period of 3 years from July 2017 to June 2020 was done. Incidence, risk factors, indication, outcome and complications of obstetric hysterectomies were evaluated. Results: A total 72 cases of obstetric hysterectomy were performed over 3 years period. Out of 72 cases, 33%, 28% and 14% cases were of peripartum hysterectomy done due to rupture uterus, PAS and PPH respectively. There was an increase in the incidence of PAS compared to previous years. There was no observed difference among patients undergoing total or subtotal hysterectomies. No difference as regard to duration of surgery, pre-operative or post-operative hemoglobin, IV fluid and blood product transfusion was noted among elective and emergency procedures. Statistically significant blood loss was observed in emergency hysterectomy compared to elective hysterectomy with p value of 0.004. An average need of transfusions was double in case of peripartum hysterectomy done for PPH compared to rupture uterus or adherent placenta. Bladder injury, burst abdomen and resuturing were three important morbidities. Maternal mortality was 2.8% in our study population. Conclusions: Emergency obstetric hysterectomy still remains a live saving procedure in case of catastrophic intractable hemorrhage and rupture uterus. Proper antenatal supervision, identification of risk factors and timely referral can reduce the incidence of associated morbidity and mortality.